Emotion Regulation as a Determinant of Decision-Making Efficiency among Engineering and Administrative Sciences Students - Bushra Ahmad Alakashee; Ali Ahmad Al-Barakat; Abdalla Falah El-Mneizel; Rommel Mahmoud Al Ali; Abdelrahim Fathy Ismail; Ali K. Abdullatif (Decision Making: Applications in Management and Engineering, 2025)
The basic aim of the research was to examine the role of emotion regulation as factor of decision-making efficiency among the administrative and engineering students. This study collected data from 300 students studying in universities of Emirates of Sharjah by using convenience sampling. The study used descriptive analytical approach through questionnaires designed to measure cognitive and behavioral aspects of emotion regulation. This research analyzed collected data through T-tests, standard deviations and arithmetic means to explore the differences on the basis of academic specialization and level of emotional regulation. The findings of the study showed that students in administrative sciences demonstrate a high level of emotion regulation, which significantly contributes to decision-making efficiency. Students in administrative sciences exhibited stronger emotional control compared to their counterparts in engineering. These findings highlight the effect of academic specializations on skills of emotional management. This improved emotional regulation helps students to keep composure under academic pressure, make well-considered decisions in situations that are challenging and approach problems logically. The results concluded that emotional regulation is important factor in the influence of decision-making efficiency of students of engineering groups. This study recommends using training and support programs with purpose to support engineering programs to enhance student’s skills of emotional regulation, expand research in terms of more universities, complementary methods and disciplines such as interviews and observations to provide comprehensive understanding of relationship between decision making efficiency and emotion regulation.